The Guinea Water Lease : Five Years On - Lessons in Private Sector Participation - Brook Cowen, Penelope J. (World Bank, Washington, DC, 2012)
In 1989, the Government of Guinea entered into a lease arrangement for private sector operation of water services in the capital city, Conakry, and sixteen other towns. The lease has been broadly successful --in the first five years, it led to a big increase in the population with access to safe water. But, because the risk sharing between the parties to the lease has proved difficult to implement and enforce, improvements have been smaller than hoped for. The author reviews the lease's performance, drawing lessons for water projects in other countries.